(untitled) (University of Khartoum Engineering Journal, 2022)
Kosti town as one of the Sudanese towns suffers from floods and storm water particularly in the rainy season due to a number of reasons such as drainage system and design and construction of the road network in the town. This paper aims to study the phenomena, determines the causes, and analyzes the results to test the hypothesis that of “the problem is mainly due to unsuitability of the planning pattern followed in the road and drainage network with the city’s topography”. To conduct this research, contour and cadastral map, of Kosti town was compiled from field survey data carried-out in 2005. The map was studied and analyzed spatially to accept or reject the hypothesis. Alternative suitable design of the road network can be suggested. Geographical information systems (GIS), i.e. ArcGIS software, were used to build triangulated irregular network (TIN). Digital terrain model (DTM) was generated for the area of the study. Based on surface analysis, it became obvious that the network follows grid-iron pattern which is not appropriate for the town topography. The study proposes designing a new road network to follow semi radial concentric spatial pattern, which is believed to be better than the existing system.